Investigation of suitable sites for wave energy converters around Sicily (Italy) - C. Iuppa; L. Cavallaro; D. Vicinanza; E. Foti (Ocean Science, 2015)
An analysis of wave energy along the coasts of Sicily (Italy) is presented with the aim of selecting possible sites for the implementation of wave energy converters (WECs). The analysis focuses on the selection of hotspot areas of energy concentration. A third-generation model was adopted to reconstruct the wave data along the coast over a period of 14 years. The reconstruction was performed using the wave and wind data from the European Centre for Medium-Range Weather Forecasts. The analysis of wave energy allowed us to characterise the most energetic zones, which are located on the western side of Sicily and on the Strait of Sicily. Moreover, the estimate of the annual wave power on the entire computational domain identified eight interesting sites. The main features of the sites include relatively high wave energy and proximity to the coast, which makes them possible sites for the implementation of WEC farms.